Distribution‐Utilization Interactions: A Race‐to‐the‐Bottom Among Oecd Countries. (29th May 2015) - Rada, Codrina; Kiefer, David
Abstract: We explore four decades of short‐ and long‐run interactions between income distribution and real economic activity for a panel of OECD countries. Our regressions suggest that the dynamic interaction of these two variables is rather complicated. Estimating the long‐run point, we argue that this equilibrium has been shifting as a matter of public policy. We hypothesize that a race‐to‐the‐bottom arises from a need to be competitive in globalized markets. We report evidence that globalization does have a negative long‐run effect on the wage share. We also find that other factors may have been important: unionization appears to be pro‐wage share, while contractionary monetary policy, financialization, and a lower relative price of investment goods tend to be anti‐wage share.